Effectiveness of Foxy Oil Combined with Oxytocin Massage on Breast Milk Production among Postpartum Mothers in Indonesia: A Quasi-Experimental Study - Silaban, Marta Armita Br; Manjorang, Novita Andriani Br; Yun, Debby Chintya; Siregar, Erin Padilla; Pratiwi, Mutia; Sihombing, Sri Nengsih (Journal of Applied Nursing and Health, 2025)
Background: Optimal breast milk production meets infants’ nutritional needs, crucial in stunting prevention. Many postpartum mothers face insufficient milk production, which can affect infant weight gain and increase the risk of stunting. The innovation of combining oxytocin massage with Foxy Oil is expected to enhance breast milk volume, frequency of wet diapers, and infant weight gain—key indicators in stunting prevention. Methods: This study used a quasi-experimental design with purposive sampling, involving 60 postpartum mothers: 30 in the intervention group and 30 in the control group. Statistical analyses were conducted using SPSS 26 for univariate and bivariate data. Data normality was tested using the Kolmogorov-Smirnov test and bivariate analysis with the Mann-Whitney test. Breastfeeding optimisation was assessed based on breast milk volume, number of wet diapers, and infant weight over one month in the working area of Tanjung Morawa Community Health Centre. The husband or a close family member performed an Oxytocin massage twice daily for 10–15 minutes. Results: Bivariate analysis after oxytocin massage showed significant effects on breast milk volume (p = 0.000), number of wet diapers (p = 0.000), and infant weight (p = 0.039). The analysis indicates that the combination of Foxy Oil and oxytocin massage positively affects breast milk production, frequency of wet diapers, and infant weight gain. Conclusion: Foxy Oil's innovation, combined with oxytocin massage, can be widely applied in midwifery practice to support successful exclusive breastfeeding and contribute to stunting prevention.